Comparative Gene Expression Analyses of Campylobacter jejuni Strains Isolated from Clinical, Environmental and Animal Sources - Azzi, Ghiwa (Université d'Ottawa / University of Ottawa, 2013)
Campylobacter species are the primary cause of bacterial food-borne diarrhoea worldwide. Comparative genomic analyses of Campylobacter strains reveal genome plasticity providing insight into the evolution of virulence traits. The goal of this study was to identify genes important for infectivity and for naturally occurring variability in phenotypic traits in C. jejuni and C. coli strains. Transcriptome and phenotype analyses were conducted to determine if genetic and phenotypic characteristics could be attributed to the source of the strains. Isolates from water sources had higher biofilm formation than animal strains. Clinical strains had decreased sensitivity to hydrogen peroxide as well as increased adherence and invasion when compared to animal strains. A number of genetic differences were observed; however, without further analysis it is difficult to determine which of these impact virulence in Campylobacter. Ultimately, this project will lead to the identification of markers associated with strains of Campylobacter causing illness.
Keywords: Campylobacter; CGF; Phenotype; Genotype; Clinical; Animal; Water; Phage; Sources; Clusters